Fractionation of soil and 15N nitrogen to separate the organic and clay interactions of immobilized N - McGill, W. B., author; Paul, Eldor A., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1976)
Labelled 15N was added to two soils in cylinders in the field, and allowed to equilibrate for two summers of crop growth. The labelled soils were fractionated to provide information on the effect of organic and inorganic colloids on the stabilization of immobilized, 15N. Organic materials removed by 0.5 N NaOH without pretreatment contained more 15N than those extracted by the same reagent following decalcification and removal of sesquioxides with dithionite and HCl. Both extracts had similar amino acid (contents) and similar degrees of hydrolability. A fractionation system using an initial 0.1 M NaOH–0.1 M Na4P2O7 extraction followed by sonication and peptization in H2O yielded a humic acid fraction and a sedimentation fraction (< 0.04 μm) which differed markedly in degree of hydrolyzability, 15N content and amino acid-N content. The N associated with inorganic colloids < 0.04 μm, and that remaining in solution after the removal of larger particles accounted for 50% of the amino acid-N in a clay soil, and 40% in a fine sandy loam soil. Removal of sesquioxides followed by a second 0.5 N NaOH extraction reduced the N content of the colloidal size fractions of both soils, indicating that amorphous iron and aluminum compounds on the surface of clays are probably the active agents in bonding organic N to inorganic colloids. It is suggested that the nonhydrolytic technique, based largely on dispersion of the inorganic–organic colloids and analyses of the sediment, could be used to interpret the fate of microbiologically immobilized N compounds in the soil. Materials removed by 0.1 M Na4P2O7 were associated with polyvalent cations in the soil. Materials such as cytoplasmic constituents, released from the biomass during ultrasonic vibration or as lytic products would be expected to be adsorbed to inorganic colloids. They should be concentrated in the < 0.04 μm-size fraction. Cell wall and other particulate debris with a faster setting velocity would be expected to appear in larger-sized sedimentation fractions.
Keywords: extraction-characterization; organic N; hydrolosis; mineralization; amino acid fraction; fractions; soil